Initial Evidence for a Telehealth Behavioral Intervention to Lower Urinary Tract Symptoms in Men - Zhang, Amy Y.; Kresevic, Denise; Shoag, Jonathan; Aaron, Siobhan; Chen, Zhengyi; Bodner, Donald R (British Journal of Healthcare and Medical Research, 2025)
Millions of American men suffer from lower urinary tract symptoms (LUTS) with a prevalence of 30% at age of 60 and older, mainly due to enlarged prostate gland—benign prostatic hyperplasia (BPH). LUTS (e.g., urgency, nocturia, weak stream, and post-void dribbles) diminish men’s quality of life significantly in later years. Medical treatments are effective, but inadequate due to poor patient compliance. A widely used behavioral approach comprising lifestyle changes through regulating fluid intake and bladder retraining (e.g., voiding schedule and pelvic floor muscle exercise) has generated promising results, but is delivered through in-person sessions, either individual or in a group setting. This delivery modality restricts intervention access by patients with diverse socioeconomic and disease conditions. Hence, we have developed a telehealth-based behavioral intervention to LUTS and tested it among 8 older men. In this pilot study, the participants received the behavioral intervention over 6 monthly group meetings via Zoom and were assessed on the severity of LUTS, symptom bother and QOL before and after the intervention. T-test showed that LUTS severity measured on the International Prostate Symptom Score (IPSS) had reduced remarkably in 6 months (mean difference=5.44, one-sided p=.0499), with a large effect size (Cohen’s d=0.865). Disease-specific and health-related quality of life assessed on IPSS-8, Visual Analogue Scale and SF20 measures indicated medium effects (Cohen’s d >0.5). Further, at the 6 months, self-efficacy (r=.86, p=.013) and adherence to voiding schedule over a 3-hour interval (r=.76, p=.047) significantly and positively correlated with mental health measured on SF-20. The findings suggest that telehealth-delivered behavioral intervention is effective in reducing LUTS and the mediating effect of behavioral change and self-efficacy requires further investigation. The study provided initial evidence to support men’s utilization of online behavioral intervention to LUTS.